Peningkatan Kemampuan Berpikir Kritis Matematis dan Habits of Mind Siswa dengan Model Creative Problem Solving - Nadia Nadia; Sehatta Saragih; Atma Murni; Adityawarman Hidayat; Sriyanti Mustafa; Yanti Yanti (Program Studi Pendidikan Matematika, FSTT, Universitas Pendidikan Mandalika, 2025)
Based on PISA results, Indonesian students’ mathematical critical thinking skills and habits of mind are still at a very low level. The study aims to investigate the impact of the Creative Problem Solving (CPS) model on enhancing these two aspects both collectively and across varying levels of Initial Mathematical Ability (IMA) among eighth-grade students in the Senapelan District of Pekanbaru City. The population of this research consisted of all eighth-grade students in the Senapelan District, and the sample included 254 students. An experimental design employing a pretest–posttest control group framework was implemented, involving four experimental classes and four control classes. Data were obtained through a mathematical critical thinking skills test based on Higher Order Thinking Skills and a habits of mind questionnaire. The results of the statistical analysis demonstrated that the CPS model significantly improved students’ mathematical critical thinking skills and habits of mind. Moreover, an interaction effect was observed between the CPS model and students’ IMA on the development of mathematical critical thinking skills, whereas no such interaction emerged concerning habits of mind. These findings indicate that the CPS model is capable of promoting the development of mathematical critical thinking skills and positive learning dispositions among Phase D students.